Cross-Cultural Pragmatics: Understanding Politeness Strategies in Intercultural Communication - Evizariza Evizariza (Penelitian dan Pengembangan Ilmu, 2024)
Intercultural communication is an important element in an increasingly connected world, where politeness plays a key role in facilitating harmonious interactions in the digital age. This research aims to explore how politeness strategies can reduce conflict in virtual interactions. The research method used involves collecting and analyzing literature from leading international databases such as Scopus, Web of Science, and Google Scholar, with a focus on studies regarding politeness strategies in cross-cultural communication. The results show that implementing effective politeness strategies can help reduce conflict and increase cross-cultural understanding in virtual contexts. The implications of this research suggest that the application of politeness techniques in digital communication is essential for managing conflict and enhancing cross-cultural cooperation.